Two Endogenous Antiangiogenic Inhibitors, Endostatin and Angiostatin, Demonstrate Biphasic Curves in their Antitumor Profiles - Kashi Javaherian; Tong-Young Lee; Robert M. Tjin Tham Sjin; George E. Parris; Lynn Hlatky (SAGE Publishing, 2011)
Angiogenesis refers to growth of blood vessels from pre-existing ones. In 1971, Folkman proposed that by choking off the blood supply to tumors, they are starved, leading to their demise. A few years ago, the monoclonal antibody Avastin became the first antiangiogenic biological approved by FDA, for treatment of cancer patients. Two other antiangiogenic endogenous protein fragments were isolated in Folkman's laboratory more than a decade ago. Here, we present a short review of data demonstrating that angiostatin and endostatin display a biphasic antitumor dose-response. This behavior is common among a large number of antiangiogenic agents and the reduced effectiveness of antiangiogenic agents at high dose rates may be due to suppression of growth of new vessels carrying the agent into the critical region around the tumor.